IMPLEMENTATION OF POSITIVE LAW IN THE LEGAL SYSTEM IN INDONESIA - Endang Pandamdari; Dyah Setyorini; Gandes Candrakirana; Ignatius Pradipa Probondaru; Dwi Saleha (RADJA PUBLIKA, 2026)
The application of positive law in the Indonesian legal system is a manifestation of the principle of a state based on law, which prioritizes certainty through written legislation. This article aims to examine the implementation of written law in Indonesia by focusing on two main issues: (1) the effectiveness of the hierarchy of laws and regulations in ensuring legal certainty, and (2) the factors that cause the gap between written legal rules ( das sollen ) and law enforcement practices in the field ( das sein ). This article shows that although the hierarchical structure has been expressly regulated in Law No. 12 of 2011, its effectiveness is still hampered by the phenomenon of hyper-regulation and disharmony between sectoral regulations that trigger legal uncertainty. In addition, the gap between das sollen and das sein is triggered by the weak moral integrity of law enforcers and the legal culture of society that is not yet fully aligned with the text of the law. Suggestions are the need to strengthen the executive review and judicial review mechanisms to synchronize overlapping regulations, as well as restructuring the development system for law enforcement officers to bridge the value of substantive justice with the text of positive law.